Health System Preparedness for Screening of Cervical Cancer: Situational Analysis in Tribal District of Gujarat State, India - Chandni P Parmar; Shahin L Saiyed; Kranti S Vora (Medsci Publications, 2020)
Introduction: Cervical cancer control program is well implemented prevention and control programme by health system in India. The study is to understand the health system situation for implementation of the programme as per WHO Framework theme and findings. The second objective is to propose Screening Model in one of the tribal district of Gujarat. Methodology: Cross sectional study was done in randomly selected blocks of Aravalli district. Data were collected by using quantitative facility checklist and questionnaires for health care providers, health official were interviewed by using semi structured questionnaire. Secondary data review was conducted to understand financial condition and reporting mechanism. Results: Majority of Health facilities have basic infrastructure to carry out screening programme for cervical cancer, although only 2% health institution are providing pap smear services. A few women are being screened. Lack of community awareness, Lack of skill based training and awareness among health care professionals for screening methods for cervical cancer were the most common reasons reported in our study. Conclusion: The study suggested urgent need to generate demand from the community by increasing community participation, provide skill based training and motivation for work among health care providers to increase uptake of screening for cervical cancer programme to reduce mortality among women.